2021
DOI: 10.31635/ccschem.021.202100956
|View full text |Cite
|
Sign up to set email alerts
|

Design of All-Fused-Ring Electron Acceptors with High Thermal, Chemical, and Photochemical Stability for Organic Photovoltaics

Abstract: High-performance donor-acceptor electron acceptors containing 2-(3-oxo-2,3-dihydro-1H-inden-1ylidene)malononitrile (INCN)-type terminals are labile toward photooxidation and basic conditions, and new molecular designs toward electron acceptors that can achieve both high power conversion efficiencies and high stability are urgently needed. By replacing the central benzene ring in the classical ladder-type n-type semiconductor, 2,2′-(indeno[1,2b]fluorene-6,12-diylidene)dimalononitrile, with the electron-rich 4,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 62 publications
0
50
0
Order By: Relevance
“…Compared with the classical carbon-bridged INCN-type acceptors, ITYM exhibits superior thermal, and chemical stability with very promising performance compared to the classical carbon-bridged NFAs. 267…”
Section: Stability Of the Oscsmentioning
confidence: 99%
“…Compared with the classical carbon-bridged INCN-type acceptors, ITYM exhibits superior thermal, and chemical stability with very promising performance compared to the classical carbon-bridged NFAs. 267…”
Section: Stability Of the Oscsmentioning
confidence: 99%
“…46 Furthermore, most emerging NFAs containing 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile (IC)-type terminals are synthesized by the Knoevenagel condensation reaction, which would make them prone to decompose under persistent light irritation. 47–53 It has been demonstrated that the photodegradation products of typical NFAs such as ITIC with IC end groups contain fused-ring isomers via a 6-e electrocyclic reaction between the dicyanomethylene unit and the thiophene ring. 50 A promising and efficient method is employing robust carbon–carbon bonds instead of the vulnerable exocyclic double bonds to link the donor unit and the acceptor unit of NFAs, which can not only lead to intrinsically stable acceptors but also successfully adjust the optoelectronic properties of NFAs.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the third-generation photovoltaic techniques, organic solar cells (OSCs) have demonstrated outstanding potentials in the fields of flexible devices, semi-transparent devices, indoor photovoltaics, and so on (Liu et al, 2021c;Dauzon et al, 2021;Kini et al, 2021;Xie et al, 2021). Excitingly, the record power conversion efficiency (PCE) of OSCs has been continuously rising in recent years, and a value exceeding 19% has been achieved already Wang et al, 2021), attributed to the innovative design and exploitation of photovoltaic materials and device architecture (Li et al, 2019;Cui and Li, 2021;Liu W. et al, 2021;Gao et al, 2021;Ren et al, 2021;Yin et al, 2021;Zheng et al, 2021). In particular, A-D-A-type nonfullerene acceptors (NFAs) play the most critical role in achieving high-performance OSCs since the emergence of the representative NFA molecule, namely ITIC, reported by Zhan et al, in 2015(Lin et al, 2015, where "D" and "A" represent the electron-donating and electron-accepting units, respectively.…”
Section: Introductionmentioning
confidence: 99%